Potret Kehidupan “Alam”: Pendidikan Yang Berwawasan Lingkungan Masyarakat Terasing Di Kampung Naga - Galuh Dwi Purwasih (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2020)
Improving the quality of human resources (HR) is a need that can not be bargained again, especially in the face of changes and developments in the field of science and technology so rapidly. This need will be felt even more when entering the era of globalization which is highly oriented to the quality of human resources according to Busro. As it is known, the globalization of information and communication has the potential to improve human resources. The need for learning to a minimum need to be improved in isolated communities through original values ​​that have been established and are rooted in people’s lives. Local knowledge or local wisdom must be included in the education curriculum as a source of innovation and skills that can be empowered for the welfare of society. Every educational process essentially is an effort to direct and mobilize two forces; on the one hand the power to preserve and on the other hand the power to advance. Fulfilling the rights of citizens to obtain educational services, especially 9-year of basic education, the Indonesian Ministry of National Education develops two channels of education, namely education through schools and non-formal education. Non-formal education consists of package A (equivalent to elementary school), package B (equivalent to junior high school), package C (equivalent to senior high school) and various life skills. A non-formal education is more flexible than formal education in terms of curriculum, time, place, students and educators. A non-formal education is one of the alternatives because it does not undermine the activities of students to learn and to pursue real life in their environments.